Análisis de las decisiones estratégicas como factor clave de la innovación y competitividad de las pequeñas empresas del sector automotriz en San Luis Potosí - Mora Guerrero, Luis Miguel (Universidad de Sonora, 2017)
This paper aims to analyze and understand the variables that affect the strategic decisions in the small business of the automotive sector of San Luis Potosi. The text begins with an introduction that contextualizes the reade  about the antecedents and importance of small companies, later establishes the theoretical framework where key variables are defined as strategic decisions, innovation and competitiveness, each of them with their models; The methodology is the next point in the development of the study, in this item the method of investigation and the form of work for the r ealization of the same is captured. The results and discussion is the part of the article where the outcome of the hypothesis and the research question is generated generating own analysis; Finally, we find the conclusions about learning and the results of the study, all of which are of great importance for the automotive sector.